Families Under Stress An Assessment of Data, Theory, and Research on Marriage and Divorce in the Military - Karney, Benjamin R. (RAND Corporation, 2007)
The authors estimate marriage and marital dissolution trends from 1996 to 2005, and the effects of recent deployments on risk of ending a marriage. Marital dissolution rates across services and components are currently similar to those seen in 1996, when the demands on the military were measurably lower. Service members who were deployed had a lower risk of subsequently ending their marriages than those who did not deploy or deployed fewer days.